Service Quality Dynamics and Bank Customer Loyalty: Study of PT Bank Central Asia Tbk Bintaro - Aprilliantoni Arifin (UNSIKA (Universitas Singaperbangsa Karawang), 2022)
ABSTRACT Aprilliantoni[1] This research aims to prove that the quality of service activities, the more performance of a bank exists. This study uses qualitative and quantitative analysis, where analysis is to determine the performance of bank services, qualitative analysis is to determine service quality, the relationship with customer loyalty, while quantitative analysis aims to determine the effect of service quality, will form perceived value which then affects satisfaction and loyalty. BCA customers in the future. Through the questionnaire data source using AMOS software. Based on the results of research that has been carried out, that PT Bank BCA Tbk in Bintaro, namely the quality of services provided to customers has a very large influence in achieving customer loyalty. This does not just happen because of the model that has been studied. The variable of service quality in achieving loyalty, was influenced by other variables. Then the variables that influence are the value perception variable and the image variable. The need to build good relationships with customers in addition to providing good service quality, so that other variables can be created. Keywords: Loyalty, Service Quality, Perceived Value, Image, BCA Bank, Structural Equation Modeling [1] Email : aprilliantonilucky@gmail.com